2021
DOI: 10.1186/s13287-021-02230-y
|View full text |Cite
|
Sign up to set email alerts
|

Anti-apoptotic effect of adipose tissue-derived stromal vascular fraction in denervated rat muscle

Abstract: Background Recovery of muscle function after peripheral nerve injury is often poor, and this can be attributed to muscle fiber atrophy and cell death. In the current study, we have investigated the effects of stromal vascular fraction (SVF) on muscle cell apoptosis and its potential to preserve muscle tissue following denervation. Methods Rat gastrocnemius muscle was denervated by sciatic nerve transection. At 2 and 4 weeks after injury, muscles we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…Previous studies have shown that the SVF secretome contains many growth factors that can stimulate cell proliferation and prevent the expression of apoptotic factors, such as Bax; this finding was reported by [79,80]. Our study recorded a significantly higher expression of Bax in the EB-treated group than in the control and SVF cotreated groups, which agrees with [23] in MS and [80] in denervated muscle.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have shown that the SVF secretome contains many growth factors that can stimulate cell proliferation and prevent the expression of apoptotic factors, such as Bax; this finding was reported by [79,80]. Our study recorded a significantly higher expression of Bax in the EB-treated group than in the control and SVF cotreated groups, which agrees with [23] in MS and [80] in denervated muscle.…”
Section: Discussionsupporting
confidence: 88%
“…Prepared enough TdT incubation buffer for all experiments according to Recombinant TdT enzyme, FITC-12-dUTP Labeling Mix and Equilibration Buffer at the ratio of 1 μL:5 μL:50 μL. Added 56 μL of dT incubation buffer to the samples, incubated at 37 °C for 1 h in the dark, washed and then added 500 μL of 10 μg/mL DAPI solution to room temperature for 8 min to stain the cells (El-Habta et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism through which UC-MSCs exert their anti-IH effects is multi-faceted. As these stem cells have the ability to differentiate into various cell types, such as smooth muscle cells, endothelial cells, and fibroblasts [ 17 , 18 ], they can promote tissue repair and inhibit the development of IH when introduced into the site of AVF creation [ 19 ]. One possible mechanism is that the transplanted stem cells release factors or cytokines that promote angiogenesis and vasculogenesis, thereby enhancing the formation of new blood vessels in the AVF.…”
Section: Discussionmentioning
confidence: 99%